Mass transfer and dispersion around an active sphere buried in a packed bed of inerts - J. M. P. Q. Delgado (2003)
The dissolution of a slightly soluble sphere buried in a packed bed of sand, throughwhich water flows is considered in the present work with due consideration given to theprocesses of transverse and longitudinal dispersion. Numerical solution of the equations wasundertaken to obtain point values of the Sherwood number, as a function of the Peclet andSchmidt numbers over a wide range of values of the relevant parameters. A correlation isproposed that describes accurately the dependence found numerically between thesedimensionless parameters.